On the regulation of marine industrial fisheries: The case of Chile - Nuñez, Javier (Estudios de Economía, 2016)
For more than 50 years Chilean marine industrial fisheries (MIF) were ruled by a criterion of “historical rights” in the issuance of fishing permits. This form of regulation was basically aimed at controlling access to the fisheries, but it did not solve the common-property issue. Through 1988 to 1991, strong controversies arose on how efficacious and efficient the prevailing regulatory instruments. However, there was neither a systematic nor an explicit discussion of alternative options leading to a definition of regulatory aims. Subsequently, the discussion centered on issues of a more institutional nature. Among them, the constitutionality of the State’s rights to limit access to fisheries and to sell full property rights over fish-stocks. On the side of the regulatory instruments, one of the key proposed reforms attempted to introduce Individual Transferrable (Catch) Quotas (ITQs) for the most important marine fisheries in the country. After more than three years of discussions, a political agreement was arrived at whereby only a partial (and non-compulsory) use of ITQs is allowed provided that a consensus concerning biological overfishing is reached. With respect to previous legal proposals, the role of ITQ’s clearly downplayed. This paper offers analytical review and discussion of this process of reforms and negotiations.